2018
DOI: 10.1088/1757-899x/298/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

The optimization of heating temperature for carbon extraction from peat soil

Abstract: Abstract. This study aims to find the optimised heating temperature for carbon extraction from peat soil. Ccarbon from peat soil was extracted by the pyrolisation process at temperature, T = 200, 300, 400, 500, 600 and 700°C for 5 hours. The carbon, C and silica, Si content extracted from peat soil at various heating temperatures were measured by using an Energy Dispersive X-Ray analyzer (EDX) at 3 points on the sample surface. High atomic percentage of carbon (95.44 %) was measured at T = 400°C, while the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…It was also observed that the peak significantly increased from 998.9cm-1 in RP to 1028.7cm -1 in PAC-D, PAC-HP, and PAC-ZC-HP. This agreed with [33] that the silica structures in PAC change with carbonization (temperature change). However, PAC-ZC showed no change at the silicate ion spectrum peak.…”
Section: Fourier-transform Infrared Spectroscopy Analysis (Ftir)supporting
confidence: 90%
See 1 more Smart Citation
“…It was also observed that the peak significantly increased from 998.9cm-1 in RP to 1028.7cm -1 in PAC-D, PAC-HP, and PAC-ZC-HP. This agreed with [33] that the silica structures in PAC change with carbonization (temperature change). However, PAC-ZC showed no change at the silicate ion spectrum peak.…”
Section: Fourier-transform Infrared Spectroscopy Analysis (Ftir)supporting
confidence: 90%
“…At PAC-D the Silica atomic concentration percentage was the highest and was seen to increase by carbonization from 16.98% and 9.19% to 29.54% and 16.61% in spots 1&2 respectively. A similar trend was also observed by [33].…”
Section: Chemical Compositionsupporting
confidence: 88%
“…Water-extractable organic carbon and nitrogen indicated a huge difference between 45 °C and 90 °C, exhibiting a constant exponential profile in response to the increasing temperature [ 37 ]. The extracted DOM yield could be enriched by the elevated temperature [ 33 , 38 ]. Besides, extractable organic carbon can be enhanced by the autoclaving processes [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%